The discovery of America and the emergence of its civilization (Journal of the College of Basic Education, 2022)
The discovery of America opened the door to finding a new continent and a new world, which led to the birth of a new civilization. Among them, especially between the English and the French, which led to the settlers uniting among themselves and their revolt against all the colonists led by George Washington. As well as the emergence of colonies in separate places according to colonial control, and soon ... these colonies turned into cities. The main objective of this research is to reveal a time period that extended from the year 1492 to 1163 AD in the American continent,